Сучасний стан та перспективи подальшого зростання мінерально-сировинного комплексу - Мартиненко, І.І. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The results of the State geological survey activity for 2005 and basic tasks on 2006 are presented. the basic financial-economic indexes and geological achievements of geological industry enterprises in implementation of searching-exploring works are shown.